Outcomes of Human Papilloma Virus Vaccination in a Private Women Health Clinic in Lebanon. (12th October 2022) - Seoud, Muhieddine; Jaafar, Iman; Ghanem, Rayan; Soubhieh, Christiane; Adra, Abdallah; Nassar, Anwar; Khalil, Ali
Abstract : Objectives . The study aims to report on the feasibility and associated adverse events of HPV-Vaccination (HPVV) in a private clinic setting in Lebanon and, when available, the results of subsequent cervical cancer screening. Methods . Opportunistic HPV vaccination is offered at the Women's Health Center of the AUBMC. We retrospectively reviewed the patients' demographic data, the incidence of adverse events, and their cytological screening. Results . A cohort of healthy women ( n = 1013) aged 26.2 years (12–54 years) were opportunistically vaccinated with one of two HPV vaccines; 845 (83.4%) received the quadrivalent vaccine (Q4V), and 151 (14.1%) received the bivalent vaccine (B2V). The majority (75.8%) received three doses while 16% received two doses. Out of these women, 26.3% (267) became sexually active postvaccination (NS2), whereas 17% (174) were sexually active prior to vaccination (SA) and the rest 57% (572) reported no sexual activity (NS1). Among the SA group, 26% (46/147) presented with abnormal cytology at time of vaccination. As for the NS2 women, 5% (14/267) had subsequently abnormal screening within 37 (12–103) months following vaccination. Conclusions . In this observational study, we report the successful introduction of HPVV with negligible adverse events. The incidence of abnormal cervical cytology was low among our patients.